Role of matrix metalloproteinases in non‐healing venous ulcers. Issue 6 (24th October 2013) - Amato, Bruno; Coretti, Guido; Compagna, Rita; Amato, Maurizio; Buffone, Gianluca; Gigliotti, Diego; Grande, Raffaele; Serra, Raffaele; de Franciscis, Stefano
Abstract: Chronic venous ulceration (CVU) of the lower limbs is a common condition affecting 1% of the adult population in Western countries, which is burdened with a high complication rate and a marked reduction in the quality of life often due to prolonged healing time. Several metalloproteinases (MMPs) such as MMP‐9 together with neutrophil gelatinase‐associated lipocalin (NGAL) appear to be involved in the onset and healing phases of venous ulcer, but it is still unclear how many biochemical components are responsible for prolonged healing time in those ulcers. In this study, we evaluate the role of MMP‐1 and MMP‐8 in long lasting and refractory venous ulcers. In a 2‐year period we enroled 45 patients (28 female and 17 male, median age 65) with CVU. The enroled population was divided into two groups: group I were patients with non‐healing ulcers (ulcers that had failed to heal for more than 2 months despite appropriate treatments) and group II were patients with healing ulcers (ulcers in healing phases). MMP‐1 and MMP‐8 were measured in fluids and tissues of healing and non‐healing ulcers by means of enzyme‐linked immunosorbent assay (ELISA) and Western blot analysis, respectively. In particular the patterns of the collagenases MMP‐1 and MMP‐8 in healing wounds were distinct, with MMP‐8 appearing in significantly greater amounts especially in the non‐healing group. Our findings suggest that MMP‐1, and MMP‐8 are overexpressed in long lasting CVU. Therefore, this dysregulation may represent the main cause of the pathogenesis of non‐healing CVU.